2021
DOI: 10.1111/jcal.12554
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the integration of technology in teaching: An analysis of the factors that increase the intention to use technologies among Italian teachers

Abstract: Background: The rapid spread of COVID-19 forced many countries to adopt severe containment measures, transferring all didactic activities into virtual environments.However, the integration of technology in teaching may present difficulties, especially in some countries, such as Italy. Objectives: The present study analyzed how the two main factors of the Technology Acceptance Model (TAM), namely perceived usefulness and perceived ease of use, combined with online teaching self-efficacy, were associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 65 publications
2
14
0
Order By: Relevance
“…One of the most important factors for teachers to consider is the extent to which it is easy to use technology (Venkatesh et al, 2003 ). According to the findings of this study, they are more likely to have the intention of using technology if they find it user-friendly, as found in previous studies (Asghar et al, 2021 ; Dindar et al, 2021 ; Luik and Taimalu, 2021 ; Menabò et al, 2021 ; Rashid et al, 2021 ; Saidu and Mamun, 2022 ; Sharma and Saini, 2022 ). It is undeniable that most of them had to rely primarily on their digital devices throughout ERT during the pandemic.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…One of the most important factors for teachers to consider is the extent to which it is easy to use technology (Venkatesh et al, 2003 ). According to the findings of this study, they are more likely to have the intention of using technology if they find it user-friendly, as found in previous studies (Asghar et al, 2021 ; Dindar et al, 2021 ; Luik and Taimalu, 2021 ; Menabò et al, 2021 ; Rashid et al, 2021 ; Saidu and Mamun, 2022 ; Sharma and Saini, 2022 ). It is undeniable that most of them had to rely primarily on their digital devices throughout ERT during the pandemic.…”
Section: Discussionsupporting
confidence: 86%
“…Of the four factors discussed on the basis of the UTAUT model, PE, EE, and SI had a significant relationship with Malaysian ESL teachers' BI to use technology in their post-COVID-19-era ESL classrooms. However, EE emerged as the most significant factor affecting their BI, which suggests that the majority of Malaysian ESL teachers are more likely to have strong intention of integrating technology into their ESL classroom if they perceive doing so to be easy and effortless, as presented in previous studies (Asghar et al, 2021 ; Dindar et al, 2021 ; Luik and Taimalu, 2021 ; Menabò et al, 2021 ; Rashid et al, 2021 ; Saidu and Mamun, 2022 ; Sharma and Saini, 2022 ). If they find technology to be user-friendly, they will be accepting of it and attempt to implement it in their daily English lessons, resulting in positive development of their attitudes (Wah and Hashim, 2021 ).…”
Section: Discussionmentioning
confidence: 59%
“…In fact, TPACK has been used as an important variable to measure teachers' online teaching readiness during the COVID-19 pandemic (Howard et al, 2021;Scherer et al, 2021). In addition, other studies of teachers amidst the pandemic demonstrated a positive influence of online teaching self-efficacy, a scale closely related to TPACK scales used in this study, and their intention to integrate technology in their practice (Chou & Chou, 2021;Menabò et al, 2021). Therefore, it is argued that teachers' TPACK efficacy can be a leading indicator of their continuous intention to work in virtual environments and there exists a strong need to enhance their TPACK for online or distance education.…”
Section: Rq2 How Does Teachers' Tpack Influence Their Continuance Int...mentioning
confidence: 83%
“…This may foster teachers' self-perception of technological proficiency, which is likely to lead to successful implementation of digital tools into educational contexts. On this matter, Menabò et al (2020) have emphasized the importance of teachers' readiness in implementing remote learning and blended teaching modalities in Italian schools to ensure that educational practices match the European recommendations for the digitalization of educational settings. This could enable Italy's recovery from falling behind other European countries in terms of didactic implementation of educational technologies (Avvisati, 2013).…”
Section: The Italian Contextmentioning
confidence: 99%